ANALISIS PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI KERJA DAN EMPLOYEE ENGAGEMENT TERHADAP KINERJA KARYAWAN (Studi pada Karyawan Non Medis RSUD K.R.M.T Wongsonegoro Semarang) - Victoria, Inge; Rahardja, Edy (Faculty of Economics and Business Diponegoro University, 2018)
The emergence of non-medical employees performance indication that has not been optimal and the presence of complaints of visitors to the dissatisfaction of services provided employees RSUD K.R.M.T Wongsonegoro be the background of this research. This study aims to examine the influence of transformational leadership style, work motivation and employee engagement on the performance of non medical employees from the background of the phenomenon that occurs in the performance of non medical employees in hospitals K.R.M.T Wongsonegoro Semarang City.The population of this research is all non medical employees RSUD K.R.M.T Wongsonegoro as many as 282 employees. Technique of sampling using technique proportional sampling and insidental sampling, with amount of sample counted 75 non-medical employees. The method of data analysis used is multiple regression with the help of SPSS program version 23.Based on multiple linear regression test, the result showed that transformational leadership, work motivation, and employee engagement have positive relation and significant influence to employee performance.